1998
DOI: 10.1159/000026519
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Whole Blood Serotonin Levels Based on a Typology of Parasuicide

Abstract: Suicidal behavior has to be considered as a multifactorial phenomenon, which can be analyzed in a classifying-phenomenological manner. We have examined the relation of parasuicide typology to whole blood concentrations of serotonin, HVA, and tryptophan in 58 patients classified into 4 groups of parasuicide typology compared to 22 nonsuicidal depressed patients and 20 healthy subjects. Suicidal patients classified as impetuous, desperate and ambivalent types had significantly reduced whole blood 5-HT levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Significantly reduced CSF 5‐HIAA levels were observed in the suicide attempt group, but this difference was completely attributable to impulsive (based upon a score of 8 or higher on the Impulsivity Rating Scale; Lecrubier, Bracconier, Said, & Payan, 1995) suicide attempters. Rilke et al (1998) examined the concentration of serotonin in blood among patients admitted for suicide attempts compared to nonsuicidal depressed subjects and healthy controls. Suicidal subjects were classified by a suicide questionnaire according to typology of attempt as either impetuous, desperate, ambivalent, or appealing (definitions for these classifications are not offered).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly reduced CSF 5‐HIAA levels were observed in the suicide attempt group, but this difference was completely attributable to impulsive (based upon a score of 8 or higher on the Impulsivity Rating Scale; Lecrubier, Bracconier, Said, & Payan, 1995) suicide attempters. Rilke et al (1998) examined the concentration of serotonin in blood among patients admitted for suicide attempts compared to nonsuicidal depressed subjects and healthy controls. Suicidal subjects were classified by a suicide questionnaire according to typology of attempt as either impetuous, desperate, ambivalent, or appealing (definitions for these classifications are not offered).…”
Section: Discussionmentioning
confidence: 99%
“…The low CSF 5-HIAA level found in suicide attempters was related to their impulsiveness, assessed by interview-based rating [Cremniter et al, 1999]; in homicide offenders, it was associated with impulse control disorder and suicide attempts [Lidberg et al, 2000]. Another study found that among suicide attempters, subjects described as ''impetuous, desperate, and ambivalent'' had lower whole blood 5-HT content than those described as ''appealing'' [Rilke et al, 1998]. In alcohol-dependent subjects, impulsive and aggressive traits might contribute significantly to the risk of suicide attempts [Koller et al, 2002].…”
Section: Impulsivitymentioning
confidence: 99%